LAC MEL Specialists Use Peer Network to Improve Quality and Use of Evidence - and Anderson, Todd M; Prevatt, Amy (USAID, 2019)
Based on consultations and stocktakings with LAC Missions, the LAC Bureau identified Mission Monitoring, Evaluation and Learning (MEL) Specialists as influential decision makers regarding data and evidence use. The LAC Bureau aims to improve the quality and use of evidence for decision making, and ultimately to improve development outcomes.